Effect of the Colloidal and Chemical Nature of Humus on the Intensity of Ice Separation in Soil - Poltev,N. F. (1970)
The quicksand state of the Northern soils in thawed form, and the high ice content of certain levels of them in frozen condition is associated to a significant extent with the hydrophilic nature of the humus of these soils. In a survey of the seasonal freezing of the soils by zones, one can in no event overlook also the zonality of their ice state, depending to a known extent on the colloidal chemical nature of the humus of the given soils. (Author) Trans. from Geocryological Studies (USSR) v7 p83-86.